2003
DOI: 10.1016/j.lts.2003.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of liver transplantation for familial amyloidotic polyneuropathy

Abstract: Patients with hereditary and primary amyloidosis were excluded from analysis. One-and 3-year survival rates after LT in MET30 patients were 100%. Before LT, five of five patients had sensorimotor neuropathy; five of five patients had diarrhea, and four of five patients had orthostatic hypotension. After LT, improvement or stabilization of neuropathy was seen in two of five patients; of diarrheal symptoms, in three of five patients; and of orthostatic hypotension, in three of four patients. One-and 3-year survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 29 publications
2
27
0
3
Order By: Relevance
“…Liver transplantation should be instrumental or potentially curative in familial amyloidosis for abolishment of the aberrant transthyretin production. Scarcity of reported cases preclude consistent conclusion but it seems that precise knowledge of specific transthyretin mutation subtype may help to differentiate the outcome of transplantation strategy (Sharma, Perri et al 2003).…”
Section: Heart Transplantation As Ultimate Surgical Option In Amyloidmentioning
confidence: 99%
“…Liver transplantation should be instrumental or potentially curative in familial amyloidosis for abolishment of the aberrant transthyretin production. Scarcity of reported cases preclude consistent conclusion but it seems that precise knowledge of specific transthyretin mutation subtype may help to differentiate the outcome of transplantation strategy (Sharma, Perri et al 2003).…”
Section: Heart Transplantation As Ultimate Surgical Option In Amyloidmentioning
confidence: 99%
“…This study showed that specific ATTR mutations do not affect the therapeutic success of CHLTx. Indeed, ALA 60 ATTR has been reported as a mutation of particularly poor prognosis and five of eight patients with ALA60 mutation described in the literature have died after ILTx (Kotani et al, 2002;Sharma et al, 2003). Moreover, the Tyr 77 ATTR (German variant) mutation is also typically associated with prominent and progressive cardiac involvement after ILTx (Garcia-Herola, 1999).…”
Section: Survival After Chltx In Attr Amyloidosismentioning
confidence: 99%
“…In the Mayo Clinic report three of the four patients with ALA 60 ATTR mutation remain alive and one died of progressive renal failure; three patients with the TYR 77 ATTR variant remain alive and had no amyloid deposition on the last endomyocardial biopsy. Autonomic disturbances, modified body mass index, duration of symptoms, polyneuropathy, disability score, orthostatic hypotension, gastrointestinal and urinary tract dysfunction are important factors in the preoperative evaluation (Grazi et al, 2003;Sharma et al, 2003;Pilato et al, 2007) and optimizing the timing for CHLTx appears to be crucial.…”
Section: Survival After Chltx In Attr Amyloidosismentioning
confidence: 99%
“…La mutación más frecuente es Val30Met. Nuestra experiencia 35 recientemente publicada consistió de 12 casos de AFP que recibieron un trasplante hepático. Cinco de ellos tenía la mutación más común, Met30 y 7 nonMet30 (Ala60, Tyr70, Gly42, Lys89).…”
Section: Amiloidosis Familiar Polineuropática (Afp)unclassified